The Phone Booth Project. Martu Media Memories: A Conversation in Three Parts. (1st December 2016) - Biddle, Jennifer; Taylor, Curtis; Hibberd, Lily
This paper is a three-way conversation between anthropologist Jennifer Biddle and the artists/collaborators of the intercultural new media installation The Phone Booth Project (2012), Curtis Taylor and Lily Hibberd. The discussion considers the importance of this collaborative, community-based, art work in terms of its capacity to reveal Martu Indigenous media history and counter-memory in the greater contemporary context of a national 'digital divide'.